Violaceous Lesions on the Leg: What Else Apart from Kaposi Sarcoma? Differential Diagnosis with a Narrative Review of the Literature - Alessandro Pileri; Gionathan Orioni; Corrado Zengarini; Vieri Grandi; Bianca Maria Piraccini; Valeria Gaspari (MDPI AG, 2023)
With this work, we aimed to review the principal benign and malignant tumors (including vascular, keratinocytic/epidermal, melanocytic, hematopoietic, and lymphoid origin), primarily affecting the leg's skin. The lesions' location can also help focus on a spectrum of differential diagnoses in clinical practice. All the diseases present the same clinical presentation characterized by erythematous to violaceous nodules. Despite the same clinical presentation, each disease's prognostic outcome and therapeutic management can be somewhat different. Since clinical diagnosis may sometimes be challenging, histology and immunohistochemistry play a fundamental role in recognizing and staging these types of lesions. Molecular studies can help to determine the exact nature of lesions with no specific characteristics. Kaposi's sarcoma is an angioproliferative neoplasm that typically occurs in the lower limbs and can enter into differential diagnosis with several other rarer skin diseases. The principal differential diagnosis concerns primary cutaneous lymphomas, of which mycosis fungoides represent the most frequent primary cutaneous T-cell lymphoma. Other rare forms include primary cutaneous B-cell lymphomas, which can be divided into indolent and aggressive forms, such as the primary cutaneous diffuse large B-cell lymphoma, leg type, and lymphomatoid papulomatosis (LyP). In the case of indolent lesions, skin-directed therapies, limited-field radiotherapy, and surgical approaches can be good options. At the same time, different management, with systemic chemotherapy and allogenic bone marrow transplant, is required with aggressive neoplasms, such as blastic plasmacytoid dendritic cell neoplasia or advanced mycosis fungoides. The dermatologist's role can be crucial in recognizing such diseases and avoiding misdiagnosis, giving the pathologist the correct clinical information for an accurate diagnosis, and starting the suitable therapy.